Monomolecular spin initiator based on metal complex, polymer with quantum coherence characteristic and preparation method of polymer

By designing metal-porphyrin or metal-phthalocyanine single-molecular spin polymers and regulating spin characteristics using polymer chains, the problem of insufficient spin life and relaxation time of organic spin quantum materials in solid state is solved, and the problem of insufficient spin life and relaxation time in solid state is achieved. Long-lived and highly coherent spin polymers suitable for a variety of quantum applications.

CN119264406APending Publication Date: 2025-01-07王明锋 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310826470.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing organic spin quantum materials have intermolecular electron transfer and spin exchange in aggregation or solid state, resulting in a shortening of quantum coherence and spin relaxation times, which is difficult to meet application needs, and the content and spatial distribution of spin molecules are difficult to control.

Method used

A series of single-molecular spin polymers with metal-porphyrin or metal-phthalocyanine as the core are designed to control the length and chemical structure of the polymer chain by introducing polymer chains, adjusting molecular spacing and spin-spin interactions, Copper porphyrin or copper phthalocyanine initiator and single-molecular spin four-arm star polymer are provided to achieve quantum coherent behavior under solid state conditions.

Benefits of technology

Under low temperature conditions, the spin life of single-molecular spin polymer can reach 40 times that of other solid organic metal frame spin materials. It has the advantages of spin life and long relaxation time without resistant magnetic dilution. It is suitable for self-health In the fields of rotary qubits, molecular magnets, nuclear magnetic or electron paramagnetic resonance imaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264406A_ABST
    Figure CN119264406A_ABST
Patent Text Reader

Abstract

The invention discloses a single-molecule spin initiator based on a metal complex, a polymer with quantum coherence characteristics and a preparation method of the polymer. The invention provides a series of single-molecule spin initiators containing metal-porphyrin or metal-phthalocyanine complexes at the centers, a polymer with quantum coherence characteristics and a preparation method of the single-molecule spin initiators. The preparation method of the metalloporphyrin or phthalocyanine single-molecule spinning polymer comprises the following step: reacting a metalloporphyrin or metal phthalocyanine initiator with a monomer compound to obtain the polymer with quantum coherence property. According to the metalloporphyrin or metal phthalocyanine initiator provided by the invention, interaction between molecular spacing and spinning can be regulated and controlled by controlling the chain length and chemical composition of a polymer, and the polymer matrix-dependent quantum coherence characteristic is shown in a solid state; the method has wide application in the technical fields of quantum calculation, quantum sensing, quantum information and biomedicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new materials, and in particular to a series of single-molecule spin initiators with metal-porphyrin and metal-phthalocyanine complexes as the core, polymers with quantum coherence characteristics, and preparation methods thereof. Background Art

[0002] Spin is one of the most important carriers of quantum information at present. Using solid-state spin as a quantum bit can directly benefit from the achievements of semiconductor micro-nano processing technology in the past half century, and provide the possibility of realizing large-scale scalable architecture and integration. Molecular spin is an important type of quantum bit building block, which has attracted widespread attention due to its diversity of chemical structure and physical controllability of spin state. Compared with inorganic spin systems, organic spin molecules have the advantages of weak spin-orbit interaction, long spin relaxation time, light weight, easy processing, and clear and controllable chemical structure. However, there are currently limited types of organic spin quantum materials at home and abroad, and device preparation and spin measurement methods still cannot meet practical needs. In addition, since most organic spin molecules have intermolecular electron transfer or spin exchange in aggregate or solid state, quantum coherence and spin relaxation time are severely shortened, and solvent dilution or doping into non-spin media is required in application. Therefore, how to design and synthesize new molecular spin materials with controllable spin lifetime and relaxation time is still a huge problem and challenge facing the field of organic spin electronics.

[0003] In order to solve these problems, researchers have tried to use physical doping, blending or solvent dilution to suppress the decoherence phenomenon caused by spin-spin interaction and prolong the spin relaxation time and quantum coherence time. For example, Gabriel Aeppli et al. co-deposited the blue pigment copper phthalocyanine (CuPc) with the structurally isomorphous but antimagnetic free base phthalocyanine (H2Pc), which reduced the spin-spin interaction and reduced the decoherence rate of the system. The quantum coherence time measured at 5 K can reach 2.6 However, this method makes it difficult to control the content and spatial distribution of spin molecules and still faces a series of challenges such as difficulty in application.

[0004] On the other hand, combining spin molecules with metal organic frameworks (MOFs) is also an effective way to improve quantum coherence. For example, Professor DE Freedman et al. prepared porphyrin units containing copper coordination into a spatially ordered framework structure. This method can achieve precise control of the spatial distribution of spin sites, and its solid state can exhibit certain quantum coherence properties. However, its phase memory time can only reach the nanosecond level. Although the spin-spin distance is increased by increasing the ligand length, its effect on the quantum coherence time ( T m) is still limited by the choice of ligand length, so the structure formed by this type of metal-organic framework has limited contribution to increasing the spin-spin distance. T m This remains a major challenge for solid-state molecular spins. Summary of the invention

[0005] The purpose of the present application is to provide a series of single-molecule spin polymers with quantum coherence and metal-porphyrin or metal-phthalocyanine complexes as the core to solve the above problems.

[0006] To achieve the above objectives, this application adopts the following technical solutions: A metal-porphyrin complex initiator, the structural formula of which is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese, X is H or other polymer chain initiating groups, and m is any integer between 0 and 9.

[0007] A metal-phthalocyanine complex initiator, the structural formula of which is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese, X is H or other polymer chain initiating groups, and m is any integer between 0 and 9.

[0008] The present application also provides a series of metal-porphyrin or metal-phthalocyanine single-molecule spin polymers, wherein the polymer center of the star-shaped polymer includes a metal-porphyrin or metal-phthalocyanine spin group; Preferably, the general structural formula of the metal-porphyrin single molecule spin polymer is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese. R is a polymer chain, preferably polyester or polyolefin.

[0009] Preferably, the general structural formula of the metal-phthalocyanine single-molecule spin polymer is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese. R is a polymer chain, preferably polyester or polyolefin.

[0010] The present application also provides a method for preparing the metal-porphyrin or metal-phthalocyanine single-molecule spin polymer, comprising: reacting the metal-porphyrin or metal-phthalocyanine initiator with a monomer compound to obtain the metal-porphyrin single molecule spin polymer; Compared with the prior art, the beneficial effects of this application include: The metalloporphyrin or metal-phthalocyanine initiator provided in the present application, after being introduced into a polymer chain, can obtain a single-molecule spin polymer with controllable chain length, chemical composition and topological morphology.

[0011] The single-molecule spin polymer provided in the present application takes transition metal copper as an example, and controls the polymer chain length and chemical structure to adjust the molecular distance and spin-spin interaction by introducing the above-mentioned copper porphyrin or copper phthalocyanine spin initiator into the polymer chain; realizes quantum coherent behavior under solid-state conditions; under the same low temperature conditions, the spin lifetime of the single-molecule spin polymer can reach 40 times that of other solid-state organic metal framework spin materials, and has the advantages of no need for antimagnetic dilution, long spin lifetime and relaxation time, etc.

[0012] The method for preparing the copper porphyrin or copper phthalocyanine initiator and the single-molecule spin four-arm star polymer provided in the present application has mild reaction conditions, simple operation and low cost.

[0013] The single-molecule spin polymer provided in the present application can be widely used in the fields of spin quantum bits, molecular magnets, nuclear magnetic resonance or electron paramagnetic resonance imaging, quantum communication and computing, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0015] Figure 1 is the structural formula of copper porphyrin series compounds Figure 2 is the structural formula of copper phthalocyanine series compounds Figure 3 is the H NMR spectrum of Cu-THPP-PCL1 in deuterated chloroform.

[0016] Figure 4 is the H NMR spectrum of Cu-THPP-PCL2 in deuterated chloroform.

[0017] Figure 5 is the H NMR spectrum of Cu-THPP-PDL in deuterated chloroform.

[0018] FIG6 is the H NMR spectrum of Cu-THPP-PDLLA in deuterated chloroform.

[0019] FIG7 is a mass spectrum of a copper porphyrin compound.

[0020] Figure 8 a is the thermogravimetric analysis curve of four copper porphyrin polymers, and b is the differential scanning calorimetry curve of four copper porphyrin polymers, showing the second heating cycle.

[0021] FIG9 shows the UV-visible spectra (a) and steady-state photoluminescence emission spectra (b) of free base porphyrin, copper porphyrin initiator and four copper porphyrin core polymers, the solution is tetrahydrofuran. The inset shows the enlarged view of the absorption band from 500-700 nm.

[0022] FIG10 shows the UV-visible spectra (a) and steady-state photoluminescence emission spectra (b) of solid films formed by spin coating THPP, Cu-THPPP, Cu-THPP-PCL1, Cu-THP P-PCL2, Cu-THPP-PDL and Cu-THPP-PDLLA (excitation wavelength is 425 nm). The inset shows a magnified view of the absorption band from 500-700 nm.

[0023] Fig. 11 Time-resolved photoluminescence decay curves of THPP (a), Cu THPP (b), Cu-THPP-PCL1 (c), Cu-THPP-PCL2 (d), Cu-THPP-PDL (e) and Cu-THPP-PDLLA (f) as well as the films at room temperature and their corresponding fitting under 375 nm excitation.

[0024] Figure 12 Continuous wave EPR spectra of four powdered polymers (Cu-THPP-PCL1, Cu-THPP-PCL2, Cu-THPP-PDL and Cu-THPP-PLLA) at different temperatures of 5 K, 20 K, 80 K, 100 K and 300 K, respectively.

[0025] Figure 13 shows the continuous wave EPR spectrum of small molecule copper porphyrin in toluene solution with a concentration of 1 mM and temperatures of 5 K, 20 K, 80 K, 100 K and 300 K.

[0026] Figure 14 Pulsed EPR characterization of copper porphyrin polymer at 5 K (a) Normalized EDFS spectrum. (b) Energy level structure of the spin Hamiltonian of a single copper porphyrin molecule. (c) Normalized Hahn echo decay curve. The solid line corresponds to the fitting curve. (d) Inversion recovery curve.

[0027] Figure 15 For Cu-THPP-PCL2 T m (a) and T 1(c) T dependence of Cu-THPP-PDL T m and T 1(d). The solid line corresponds to the fitted curve. The inset shows the zoomed-in spectral features. 5 K, 20 K, 40 K and 77 K are selected for display.

[0028] Figure 16 Cu-THPP-PCL2 and Cu-THPPP-PDL T 1 and T m Temperature dependence diagram of .

[0029] Figure 17 shows the pulse sequence used in the quantum manipulation experiment at 5 K. (a) The pulse sequence used in the measurement. (b, c, d, f) Rabi oscillations attenuated by various microwaves for Cu-THPP-PCL1, Cu-THPP-PCL2, Cu-THPP-PDL, and Cu-THPP-PDLLA, respectively.

[0030] FIG. 18 is a hydrogen nuclear magnetic resonance spectrum of CuPc-PCL in deuterated chloroform.

[0031] FIG. 19 is a hydrogen nuclear magnetic resonance spectrum of CuPc-PDLLA in deuterated chloroform. DETAILED DESCRIPTION

[0032] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0033] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0034] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0035] A metal porphyrin initiator, the structural formula of which is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese, X is H or other polymer chain initiating groups, and m is any integer between 0 and 9.

[0036] A metal phthalocyanine initiator, the structural formula of which is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese, X is H or other polymer chain initiating groups, and m is any integer between 0 and 9.

[0037] The present application also provides a series of metal-porphyrin or metal-phthalocyanine single-molecule spin polymers, wherein the polymer center of the star-shaped polymer includes a copper porphyrin spin group; preferably, the general structural formula of the metal-porphyrin single-molecule spin polymer is: ; Preferably, the general structural formula of the metal phthalocyanine single-molecule spin polymer is: It should be noted that in the general structural formula of the above polymer, "R" represents the repeating unit and its attached groups in the polymer chain.

[0038] Wherein, M is a metal element, and may be preferably copper, vanadium oxide, iron, or manganese. R is a polymer chain, and may be preferably polyester or polyolefin, and m and n are each independently a positive integer. The present application also provides a method for preparing the metalloporphyrin single molecule spin polymer, comprising: reacting the metal porphyrin initiator and the monomer compound to obtain the metal porphyrin single molecule spin polymer; The above-mentioned solid materials include, but are not limited to, application materials in the fields of spin electronic devices, molecular magnets, nuclear magnetic resonance or electron paramagnetic resonance imaging, quantum communication and computing, and spin electronics.

[0039] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0040] Example 1 This embodiment provides a single molecule spin metal porphyrin initiator, taking copper porphyrin as an example, and its structural formula is: ; Wherein, m = 9 and n is a positive integer. Example 2

[0041] This embodiment provides a series of single-molecule spin metal porphyrin four-arm star polymers, taking transition metal copper as an example, and the general structural formula thereof is: ; Wherein, m = 9 and n is a positive integer.

[0042] This embodiment also provides a method for preparing the above-mentioned single-molecule spin metal porphyrin polymer, taking copper porphyrin as an example, the specific method is as follows: Under nitrogen atmosphere, dry copper porphyrin initiator (100 mg, 0.07 mmol), catalyst 1,5,7-triazabicyclo[4,4,0]dec-5-ene (TBD) (195 mg, 1.4 mmol), monomer ε-caprolactone (2.24 mL, 19 mmol) and 5 mL dry anisole were added to a 20 mL baked Schlenk bottle, and the polymerization was carried out by stirring at room temperature for 24 hours. The reaction mixture was then dissolved with dichloromethane and precipitated in cold methanol three times. The solid obtained by centrifugation was dried in a vacuum until constant weight to obtain a red fine powder (yield: 15%). Relative number average molecular weight ( n ) is 11.0 kg / mol, molecular weight distribution ( w / n ) is 1.20. It is denoted as Cu-THPP-PCL1. Example 3

[0043] This embodiment provides a single-molecule spin metal-porphyrin polymer, taking copper-porphyrin as an example, and its general structural formula is: ; Wherein, m = 9 and n is a positive integer.

[0044] This embodiment also provides a method for preparing the above-mentioned single-molecule spin metal porphyrin polymer, taking copper porphyrin as an example, the specific method is as follows: Under nitrogen atmosphere, dry copper porphyrin initiator (100 mg, 0.07 mmol), catalyst TBD (195 mg, 1.4 mmol), monomer ε-caprolactone (4.48 mL, 38 mmol) and 10 mL dry anisole were added to a 20 mL baked Schlenk bottle, and the polymerization was carried out by stirring at room temperature for 48 hours. The reaction mixture was then dissolved with dichloromethane and precipitated in cold methanol three times. The solid obtained by centrifugation was dried in a vacuum until constant weight to obtain a red fine powder (yield: 36%). Relative number average molecular weight ( n ) is 28.0 kg / mol, molecular weight distribution ( w / n ) is 1.24. It is recorded as Cu-THPP-PCL2. Example 4

[0045] This embodiment provides a single-molecule spin metal porphyrin polymer, taking copper porphyrin as an example, and its structural formula is: ; Wherein, m = 9 and n is a positive integer.

[0046] This embodiment also provides a method for preparing the above-mentioned single-molecule spin metal porphyrin polymer, taking copper porphyrin as an example, the specific method is as follows: Different from Example 2, the monomer compound ε-caprolactone was replaced with ε-decanoic acid, and no solvent was added, and the polymer Cu-THPP-PDL was finally obtained with a yield of 45%. n ) is 16.0 kg / mol, and the molecular weight distribution ( w / n ) was 1.25. The polymer was recorded as Cu-THPP-PDL. Example 5

[0047] This embodiment provides a single-molecule spin metal porphyrin polymer, taking copper porphyrin as an example, and its structural formula is: ; Wherein, m = 9 and n is a positive integer.

[0048] This embodiment also provides a method for preparing the above-mentioned single-molecule spin metal porphyrin polymer, taking copper porphyrin as an example, the specific method is as follows: Different from Example 2, the monomer ε-caprolactone was replaced by L-lactide, the solvent was replaced by dry dichloromethane, and since the non-chiral catalyst TBD was used, the polymer Cu-THPP-PDLLA was finally obtained with a yield of 13%. n ) is 15.0 kg / mol, and the molecular weight distribution ( w / n ) was 1.15. The polymer was recorded as Cu-THPP-PDLLA. Example 6

[0049] This embodiment provides a single-molecule spin metal phthalocyanine initiator, taking copper phthalocyanine as an example, and its structural formula is: ; where m = 9. Example 7

[0050] This embodiment provides a series of single-molecule spin metal phthalocyanine eight-arm star polymers, taking transition metal copper as an example, and the general structural formula thereof is: ; Wherein, m = 9 and n is a positive integer.

[0051] This embodiment also provides a method for preparing the above-mentioned single-molecule spin metal phthalocyanine polymer, taking copper porphyrin as an example, the specific method is as follows: Under nitrogen atmosphere, dry initiator (Cu-Pc) (50 mg, 0.03 mmol), catalyst Sn(Oct)2 (3 mg), monomer ε-caprolactone (2.24 mL, 19 mmol) and 3 mL dry toluene were added to a 20 mL baked Schlenk bottle, and the polymerization was carried out by stirring at 120 degrees Celsius for 18 hours, and then the reaction mixture was dissolved with dichloromethane and precipitated in cold methanol three times. The solid obtained by centrifugation was dried in a vacuum until constant weight to obtain; green fine powder (yield: 65%). Relative number average molecular weight ( n) is 19.9 kg / mol, molecular weight distribution ( w / n) is 1.28. It is denoted as CuPc-PCL. Example 8

[0052] This embodiment provides a single-molecule spin metal phthalocyanine polymer, taking copper phthalocyanine as an example, and its structural formula is: ; Wherein, m = 9 and n is a positive integer.

[0053] This embodiment also provides a method for preparing the above-mentioned single-molecule spin metal porphyrin polymer, taking copper phthalocyanine as an example, the specific method is as follows: Under nitrogen atmosphere, dry initiator (Cu-Pc) (50 mg, 0.03 mmol), catalyst Sn(Oct)2 (3 mg), monomer DL-lactide (2.74 g, 19 mmol) and 3 mL of dry toluene were added to a 20 mL baked Schlenk bottle, and the polymerization was carried out by stirring at 120 degrees Celsius for 18 hours, and then the reaction mixture was dissolved with dichloromethane and precipitated in cold methanol three times. The solid obtained by centrifugation was dried in a vacuum until constant weight to obtain; green fine powder (yield: 60%). Relative number average molecular weight ( n) is 6.4 kg / mol, molecular weight distribution ( w / n) is 1.19. It is denoted as CuPc-PDLLA.

[0054] Figure 8 shows the thermogravimetric analysis of the polymers. The initial weight losses of Cu-THPP-PCL1 and Cu-THPP-PCL2 at 420 °C were 20%, Cu-THPP-PDL at 610 °C was 7%, and Cu-THPP-PDLLA at 320 °C was 15%. T m The values ​​are 53 and 54 °C, respectively, corresponding to their molecular weight (MW) sequences. It was found that the T g Cu-THP-PDLLA showed T at 39 °C. g Cu-THP-PDL and Cu-THPP-PDLLA have no melting peaks. 1 The H NMR spectrum showed multiple signals from 5.13 to 5.23 ppm, indicating the presence of a non-single stereoregular arrangement. Therefore, the polyester series obtained from L-lactic acid was named PDLLA.

[0055] The absorption spectrum in solution and the steady-state fluorescence emission spectrum are shown in Figure 9. Typical UV-visible absorption bands of porphyrin were observed, with one Soret band at 419 nm and four Q bands at 435, 508, 591, and 708 nm. Copper porphyrin showed two Q bands at 485 and 564 nm, and the optical properties of the polymer were consistent with those of the copper porphyrin initiator.

[0056] Figure 10 shows the UV-visible absorption and steady-state fluorescence emission spectra in the films. The porphyrin film is slightly red-shifted, with the S band at 437 nm and the Q bands at 440 nm, 515 nm, 587 nm, and 701 nm. The copper porphyrin film shows a Q band at 488 nm. The absorption spectra of the polymer films follow the same trend as the solution, with the Soret and Q bands at 419 nm and 544 nm, respectively.

[0057] According to the excitation spectrum, the excitation wavelength of porphyrin was selected as 425 nm. Only the free radical porphyrin showed strong red fluorescence under UV light. The results were consistent with the fluorescence spectrum, and the coordination with the metal led to the fluorescence quenching of porphyrin. All spectra showed a broad peak with a maximum emission in the range of 652–663 nm and a second emission peak around 725 nm. In addition, Cu-THPP, Cu-THPP-PCL1, and Cu-THPP-PDLLA showed a shoulder peak centered at about 610 nm. In the film, all copper-containing compounds showed a red shift compared to the solution sample. The Cu-THPP film showed a maximum emission at 775 nm. The four polymers containing copper porphyrin showed a broad peak with a maximum emission range of 807-838 nm, which resulted in a large Stokes shift of about 400 nm. Several factors such as the rigidity of the compounds, intramolecular vibration, or relaxation may lead to this difference in Stokes shift.

[0058] Figure 11 shows the fluorescence lifetime (τ) measured at room temperature. According to the fitting results, the free base porphyrin (THPP) shows the shortest lifetime below 2 ns. The average lifetime (τ) of Cu-THPP-PCL2 and Cu-THPP-PDL at room temperature is ave ) is in the range of 40-70 ns, while for Cu-THPP-PCL1 and Cu-THPP-PDLLA at room temperature, τ ave The short lifetime of THPP is a result of quenching due to energy transfer and singlet-singlet annihilation caused by intermolecular interactions between porphyrin units. The relatively long lifetime measured for the polymer sample further supports that in the polymer structure, the porphyrin units are mainly isolated monomers, and their arrangement prevents interaction between them. Therefore, in the solid state, the polymer structure effectively suppresses the intermolecular aggregation of copper-containing porphyrins and prolongs the lifetime of copper porphyrins as fluorescent emitters.

[0059] FIG12 shows the continuous wave electron paramagnetic resonance spectra of four copper porphyrin four-arm star polymers at different temperatures.

[0060] Figure 12 shows the steady-state EPR spectra of four copper porphyrin complexes, Cu-THPP-PCL1, Cu-THPP-PCL2, Cu-THPP-PDL, and Cu-THPP-PDLLA, at different temperatures. The Cu-THPP structure exhibits a typical copper porphyrin EPR spectrum. As the temperature decreases, the relative intensity of the signal in Cu-THPP-PCL2 decreases (Figure 12b). In contrast, the signal intensity of Cu-THPP-PDL (Figure 12c) and Cu THPP PDLLA (Figure 12d) increases significantly with decreasing temperature. In addition, it is observed that the signal intensity of Cu-THPP-PCL1 (Figure 12a) increases from 5 K to 20 K, and exhibits a peak at 20 K, and then decreases with increasing temperature. At 300 K, there is obvious hyperfine coupling in the high molecular weight Cu-THPP-PCL2 (Figure 12b), which may be attributed to the better diamagnetic dilution effect due to the longer chain length, which reduces the interaction between spins. Interestingly, this change was also observed in the soft matrix Cu-THP-PDL (Figure 12c).

[0061] Figure 13 shows the continuous wave electron paramagnetic resonance spectra of copper porphyrin molecules (Cu-THPP) in toluene solution at different temperatures. The concentration is 1 mM.

[0062] The continuous wave electron paramagnetic resonance signal intensity of Cu-THPP in toluene solution decreases as the temperature increases from 5 K to 300 K, the spectral line is significantly broadened, and the nitrogen hyperfine line disappears completely. Figure 14 shows the pulsed electron paramagnetic resonance characterization at a temperature of 5 K.

[0063] Figure 14 shows the quantum coherence properties of the four polymers by pulsed EPR. The X-band echo detection field scan (EDFS) EPR spectra were recorded using a standard Hahn echo sequence. At low temperatures, the four polymers all exhibit quantum coherence (Figure 14a). The Hahn echo curves indicate the presence of a decoherence process (Figure 14c). The fitting results correspond to the coherence time T m . Cu-THPP-PCL1, Cu-THPP-PCL2, Cu-THPP-PDL, Cu-THPP-PLLA T m The values ​​are 0.46 , 2.11 , 0.99 and 0.55 , which increases with the increase of polymer chain length (Figure 14c). T mThis extension of may be due to the decrease in spin concentration and the weakening of electron-spin-electron-spin interactions. When the chain lengths are almost equal, the quantum coherence time of Cu-THPP-PDL is T m The spin-lattice relaxation time ( T 1), Cu-THPP-PCL1, Cu-THPP-PCL2, Cu-THPP-PDL and Cu-THPP-PDLLA corresponding T 1 value is 21.50 ,247.50 , 238.53 and 52.25 (Figure 14d). T 1 to T m Several orders of magnitude higher. T m Not affected T This observation of 1 limitation can be attributed to the nuclear spin of the polymer. These results suggest that copper porphyrin four-arm star polymers can reach the material's practicality in research and various applications.

[0064] Figure 15 shows the Cu-THPP-PCL2 and Cu-THPP-PDL T m and T 1 Temperature dependence of the relationship.

[0065] Figure 16 shows the Cu-THPP-PCL2 and Cu-THPP-PDL T m and T Temperature dependence of 1. 5 K, 20 K, 40 K and 60 K are selected for presentation.

[0066] Figure 15 shows the Cu-THPP-PCL2 and Cu-THPP-PDL T m Thermal changes in the temperature range (5−77 K) compared to T 1 shows a weak temperature dependence (Fig. 15a, b and Fig. 16), while Cu-THPP-PCL2 T m Values ​​range from 0.65 to 2.11 Within the range, Cu-THPP-PDL T m Value is between 0.50-1.06 Inversion recovery experiments were also performed in the range of 5−77 K to study T 1 (Fig. 15c, d). The obtained saturation recovery trace was fitted with a single exponential equation, and the extracted T 1 values ​​are shown in Figure 16. T1 drops rapidly from the maximum value at 5 K to 77 K.

[0067] Figure 17 shows the Rabi oscillation experiment at 5 K.

[0068] The Rabi oscillation experiment verified the possibility of copper porphyrin-centered star polymers as quantum bits. When a pulse with increasing length is added before the normal Hahn echo sequence, a continuous decay oscillation of the echo intensity is observed when the B1 field is given. Rabi oscillations were observed in all four copper porphyrin core star polymers Cu-THPP-PCL1, Cu-THPP-PCL2, Cu-THPP-PDL and Cu-THPP-PDLLA.

[0069] Comparative Example 1 Compared with the continuous wave electron paramagnetic resonance spectrum of the polymer, the continuous wave electron paramagnetic resonance spectrum of the copper-porphyrin small molecule initiator (Cu-THPP) in the frozen toluene solution shows a complete absence of nitrogen hyperfine lines. These results indicate that it is difficult for toluene as a solvent molecule to achieve the quantum coherence characteristics of spin molecules, and also confirm the unique role of the introduction of polymer chains in regulating the quantum coherence properties of such molecular spins.

[0070] This application uses molecular design synthesis and chemical synthesis methods to introduce single-molecule metal porphyrin or metal phthalocyanine spin primitives into a polymer matrix, and its molecular structure is clear and controllable. Taking transition metal copper as an example, by changing the chain length, composition and physicochemical properties of the polymer, the spin characteristics of organic molecules can be regulated, and the spin lifetime and relaxation time can be increased. Under solid-state conditions, the Rabi oscillation curves of four polymers were measured by pulsed electron paramagnetic resonance technology, which indicates the existence of quantum coherent behavior, illustrating the potential of such single-molecule spin metal porphyrin or metal phthalocyanine polymers as solid-state spin molecules.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0072] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A metalloporphyrin initiator, characterized in that: Its general structural formula is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese, X is H or other polymer chain initiating groups, and m is any integer between 0 and 9.

2. A metal-porphyrin single molecule spin polymer, characterized in that The center of each star-shaped polymer is a metal-porphyrin group, and the general structure of the metal-porphyrin is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese. R is a polymer chain, preferably polyester or polyolefin.

3. A method for preparing the metal-porphyrin single-molecule spin polymer according to claim 2, characterized in that: include: The metal-porphyrin initiator described in claim 1 and monomer compounds such as ε-caprolactone, ε-decanoic acid and lactide are heated and reacted under the action of a first catalyst to obtain the metal-porphyrin single molecule spin polymer.

4. The preparation method according to claim 3, characterized in that: The heating reaction further comprises: The reaction system was cooled to room temperature and added into iced anhydrous methanol under stirring to obtain a precipitate.

5. A metal phthalocyanine initiator, characterized in that Its general structural formula is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese, X is H or other polymer chain initiating groups, and m is any integer between 0 and 9.

6. A metal-phthalocyanine single-molecule spin polymer, characterized in that The center of each star-shaped polymer is a metal-phthalocyanine group, and the general structure of the metal-phthalocyanine is: ; Wherein, M is a metal element, preferably copper, vanadium oxide, iron, or manganese. R is a polymer chain, preferably polyester or polyolefin.

7. A method for preparing the metal-phthalocyanine single-molecule spin polymer according to claim 6, characterized in that: include: The metal-phthalocyanine initiator described in claim 5 and monomer compounds such as ε-caprolactone, ε-decanoic acid and lactide are heated to react under the action of a second catalyst to obtain the metal-phthalocyanine single molecule spin polymer.

8. The preparation method according to claim 7, characterized in that: The heating reaction further comprises: The reaction system was cooled to room temperature and added into iced anhydrous methanol under stirring to obtain a precipitate.